Functional Properties of Adlay Flour (Coix lacryma-jobi L. var. Ma-yuen) Resulting from Modified Durations of Fermentation Using Rhizopus oligosporus - Ardiyan Dwi Masahid; Maria Belgis; Helyas Vintan Agesti (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Adlay is a nutritious grain that has the potential as an alternative food because it has a high protein and fat content of 14.10% and 7.90%, respectively. The use of Adlay as flour still has a weakness, namely the functional properties of Adlay flour such as low swelling power. One way to improve the characteristics of Adlay flour is by fermentation using Rhizopus oligosporus. The fermentation duration is the time that allows changes in the characteristics of the flour due to the fermentation. This study aims to determine the effect of differences in fermentation duration using Rhizopus oligosporus on the physical, chemical, and functional characteristics of Adlay flour produced from fermented Adlay seeds. This study used one factor, namely the lengths of fermentation for 0, 12, 24, 30, 36 and 48 hours. The analysis in this study included whiteness, yield, pH, water content, ash content, protein content, fat content, carbohydrate content, swelling power and solubility, oil holding capacity (OHC) and water holding capacity (WHC). The results have shown that the longer the fermentation duration the lower rate of whiteness, pH, yield, water content, fat content, and carbohydrate content will become, while some functional properties of Adlay flour become better with increasing values of ash content, protein content, swelling power, solubility, Oil Holding Capacity (OHC), and Water Holding Capacity (WHC).